Leukoaraiosis and Stroke - Eric E. Smith (2010)
Leukoaraiosis is a common finding in stroke patients and has been strongly associated with risk of incident stroke and dementia. Leukoaraiosis may also be an independent predictor of stroke outcomes. There is increasing evidence from neuroimaging to support the concept that some leukoaraiosis is caused by white matter infarcts, which may be particularly frequent in patients with aggressive small vessel diseases such as cerebral amyloid angiopathy. The relatively similar distribution of leukoaraiosis regardless of the distribution of vascular pathology suggests a conserved vulnerability to white matter injury across various vascular diseases, possibly related to resting patterns of blood flow. More insights into the pathophysiology of leukoaraiosis are sorely needed to reduce the burden of disability associated with this common condition.